PENANDA IDENTITAS DALAM PENAMAAN WILAYAH ADMINISTRASI DI KABUPATEN SANGGAU - Satwiko Budiono; Winci Firdaus (Masyarakat Linguistik Indonesia, 2022)
Markers of the identity of a group can be seen from the language and culture. A group that lives in an area usually names its territory using their language and cultural characteristics of the place. However, heterogeneity in Indonesia society makes the naming of regions experience changes and shifts over time. This can be seen from the naming of the administrative area in Sanggau Regency, West Kalimantan Province. As a border area between Indonesia and Malaysia, the naming of administrative areas becomes necessary and important to be preserved as an identity marker. In this regard, this study explores the naming of administrative areas in Sanggau Regency. This study aims to describe the pattern of naming administrative areas as language documentation, explore identity markers in naming administrative areas, and preserve language and cultural characteristics in naming administrative areas. The research method is based on toponymy research with descriptive qualitative analysis. Data collection techniques using questionnaires and interviews. The research data includes the naming of sub-village, village, and districts in Sanggau Regency, West Kalimantan Province. The research respondents were 50 people who were selected proportionally based on their language and ethnicity. The results of this study are the naming of administrative areas in Sanggau Regency has several semantic categories, such as fruit, rivers, trees or plants, places, people, ethnics, objects, and animals. In terms of language, the naming of the administrative area in Sanggau Regency comes from Malay, Dayak, Javanese, and Indonesian. This result was obtained from local knowledge, although not all administrative area names were explored. The number of administrative areas that have not been explored makes language documentation efforts need to be followed up by the local government.Â